Influencing factors of lymphopenia after conventional fractionated whole-breast radiotherapy following breast-conserving surgery for early breast cancer: a retrospective study - Sun, Yang; Chen, Yanan; Liu, Ting; Pan, Pan; Gu, Yongjuan; Liang, Xuexue; Shen, Dong; Xu, Lixian (Frontiers in Oncology, 2026)
ObjectiveTo explore the risk factors for grade 2 or higher lymphocytopenia during whole-breast radiotherapy after breast-conserving surgery for breast cancer.MethodsA total of 112 patients who underwent whole-breast radiotherapy after breast-conserving surgery for breast cancer in our department from June 2019 to June 2024 were selected and divided into the no/mild lymphopenia group (no or grade 1 lymphocytopenia, 48 cases) and moderate/severe lymphopenia group (grade 2 or higher lymphocytopenia, 64 cases). Univariate and multivariate logistic regression analyses were performed on the clinical data and dosimetric parameters of the two groups to identify the independent risk factors for grade 2 or higher lymphocytopenia. The predictive efficacy of the risk factors was established using the receiver operating characteristic (ROC) curve.ResultsUnivariate logistic regression analysis indicated that there were statistically significant differences between the two groups in terms of whether they received chemotherapy, the quantity of chemotherapy cycles, initial lymphocyte count prior to chemotherapy and radiotherapy, and dosimetric parameters, such as the mean dose (Dmean), doses received by 40%, 60%, and 80% of the sternum volume (D40, D60, D80), and volume of the sternum receiving 5 Gy (V5) (OR range: 0.092~3.927, P < 0.05). Multivariate logistic regression analysis revealed that lymphocytopenia prior to chemotherapy and an elevated D80 of the sternum were independent predictors for grade 2 or higher lymphocytopenia (OR range: 0.287~1.517, P < 0.05). The ROC curve analysis determined that the optimal threshold values for initial lymphocyte count prior to chemotherapy and D80 of the sternum were 1.775 × 109/L and 2.85 Gy, respectively. The area under the curve (AUC) values were 0.787 and 0.7, with corresponding sensitivities of 82.8% and 75.6%, and specificities of 70.4% and 76.7%, respectively.ConclusionLymphocytes <1.775 × 109/L before chemotherapy and D80 of the sternum >2.85 Gy are independent risk factors for grade 2 or higher lymphocytopenia during whole-breast radiotherapy after breast-conserving surgery for breast cancer.